Joint 9D Receiver Localization and Ephemeris Correction with LEO and 5G Base Stations - Emenonye, Don-Roberts; Dhillon, Harpreet S.; Buehrer, R. Michael (MILCOM IEEE Military Communications Conference, 2024)
In this paper, we use the Fisher information matrix (FIM) to analyze the interaction between low-earth orbit (LEO) satellites and 5G base stations in providing 9D receiver localization and correcting LEO ephemeris. First, we give a channel model that captures all the information in the LEO-receiver, LEO-BS, and BS-receiver links. Subsequently, we use FIM to capture the amount of information about the channel parameters in these links. Then, we transform these FIM for channel parameters to the FIM for the 9D (3D position, 3D orientation, and 3D velocity estimation) receiver localization parameters and the LEO position and velocity offset. Closed-form expressions for the entries in the FIM for these location parameters are presented. Our results on identifiability utilizing the FIM for the location parameters indicate: i) with one LEO, we need three BSs and three time slots to both estimate the 9D location parameters and correct the LEO position and velocity, ii) with two LEO, we need three BSs and three time slots to both estimate the 9D location parameters and correct the LEO position and velocity, and iii) with three LEO, we need three BSs and four-time slots to both estimate the 9D location parameters and correct the LEO position and velocity. We notice from the Cramer Rao lower bound that the operating frequency and number of receive antennas have negligible impact on the estimation accuracy of the orientation of the receiver and the LEO velocity, respectively.